Characteristics of patients in routine psycho-oncological care, and changes in outcome variables during and after their treatment. Issue 10 (2nd October 2016) - Garssen, Bert; Van der Lee, Marije; Van der Poll, Amber; Ranchor, Adelita V.; Sanderman, Robbert; Schroevers, Maya J.
Abstract : Objective : The primary aim of this study was to determine the characteristics of clients and interventions in routine psycho-oncological care. The secondary aim was to determine the course of symptomatology during and after the psychological interventions. Design : During a period of nine months, all clients who sought help in one of the seven psycho-oncological care institutes in the Netherlands were approached to participate in the present study ( N  = 483). Information was gathered with respect to demographic and medical characteristics, and type and duration of the interventions. In addition, depression, anxiety, well-being, quality of life, fatigue and daily function were determined before interventions and three and nine months later. Results and conclusions : Compared to the Dutch cancer population, patients in psycho-oncological care were more often young and female. Compared to the general Dutch population, they were highly educated and were more likely to have a partner. Clinical levels of depression, anxiety and/or fatigue were found among 83% of the patients. After three months, only 23% had completed their intervention; this figure was 62% after nine months. Symptoms decreased significantly for all outcome variables. An importance difference with randomised controlled trials is the low session frequency and the long intervention time of patients in clinical care.